Can't touch this. Issue 1 (10th May 2019) - Clarke, Amy; King, Stuart; Leach, Andrew; Van Acker, Wouter
Abstract : Australia's laid-back, sun-drenched beach lifestyle has been a celebrated and prominent part of its official popular culture for nigh on a century, and the images and motifs associated with this culture have become hallmarks of the country's collective identity. Though these representations tend towards stereotype, for many Australians the idea of a summer holiday at the beach is one that is intensely personal and romanticised – its image is not at all urbanised. As Douglas Booth observed, for Australians the beach has become a 'sanctuary at which to abandon cares – a place to let down one's hair, remove one's clothes […] a paradise where one could laze in peace, free from guilt, drifting between the hot sand and the warm sea, and seek romance'. 1 Beach holidays became popular in the interwar years of the twentieth century, but the most intense burst of activity – both in touristic promotion and in the development of tourism infrastructure – accompanied the postwar economic boom, when family incomes were able to meet the cost of a car and, increasingly, a cheap block of land by the beach upon which a holiday home could be erected with thrift and haste. In subtropical southeast Queensland, the postwar beach holiday became the hallmark of the state's burgeoning tourism industry; the state's southeast coastline in particular benefiting from its warm climate and proximity to the capital, Brisbane. It was here – along the evocatively named Gold Coast (to Brisbane's south) and Sunshine Coast (to its north) [1] – that many families experienced their first taste of what is now widely celebrated as the beach lifestyle [2]. As one reflection has it:In the era before motels and resorts, a holiday at the Gold and Sunshine coasts usually meant either pitching a tent and camping by the beach or staying in a simple cottage owned by family or friends […] Simplicity, informality, individuality […] were the hallmarks of these humble places. 2